2022
DOI: 10.1039/d2ee01774a
|View full text |Cite
|
Sign up to set email alerts
|

A high-rate and high-efficiency molten-salt sodium–oxygen battery

Abstract: A molten-salt Na–O2 battery featuring a liquid Na negative electrode and Ni positive electrode was found to form Na2O2 on discharge, enabled by nitrate redox where NO3− is reduced to Na2O and NO2−, then reactions with O2 produce Na2O2 and reform NO3−.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Molten salts comprised of redox active nitrate anions can function as a standalone S-I battery reaction, [115] as well as a redox active electrolyte in molten-salt metal-O 2 batteries. [116,117,119,139,140] Our recent work on molten salt Li-O 2 [117] and Na-O 2 [116] batteries has demonstrated that nitrate-based molten salt electrolytes can enable high performance metal-O 2 batteries. For instance, molten-salt Li-O 2 batteries with positive electrodes featuring nanoparticle Ni [117] could be discharged at rates up to 2.0 mA cm −2 geo with areal capacities up to 17 mAh cm −2 geo (Figure 6d).…”
Section: Redox Active Molten Salt Electrolytes In Metal-o 2 Batteriesmentioning
confidence: 99%
See 3 more Smart Citations
“…Molten salts comprised of redox active nitrate anions can function as a standalone S-I battery reaction, [115] as well as a redox active electrolyte in molten-salt metal-O 2 batteries. [116,117,119,139,140] Our recent work on molten salt Li-O 2 [117] and Na-O 2 [116] batteries has demonstrated that nitrate-based molten salt electrolytes can enable high performance metal-O 2 batteries. For instance, molten-salt Li-O 2 batteries with positive electrodes featuring nanoparticle Ni [117] could be discharged at rates up to 2.0 mA cm −2 geo with areal capacities up to 17 mAh cm −2 geo (Figure 6d).…”
Section: Redox Active Molten Salt Electrolytes In Metal-o 2 Batteriesmentioning
confidence: 99%
“…Such “dual mediator” [ 113,114 ] systems showed enhanced cycle life such as a Li–O 2 batteries with stable cycling over 90 cycles reported by Liang et al., [ 111 ] where cycling became limited by the Li metal negative electrode. Moreover, redox‐active nitrate molten salts [ 115 ] have also been leveraged to enable high rate (10 mA cm −2 geo ) [ 116 ] and high capacity (17 mAh cm −2 geo ) [ 117 ] metal‐oxygen batteries, with low overpotentials (≈0.1 V voltage difference between discharge and charge [ 118 ] ) and high cycle life (>150 cycles [ 119 ] ). In this section, we consider the influence of such redox active electrolyte species on the rate, reaction pathways and reversibility of Li–O 2 and Na–O 2 batteries.…”
Section: Redox Mediators and Redox Active Molten Salt Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations
“…This information is important to adequately describe the molecular structure and dynamics of such systems. At present, infrared (IR) and Raman spectra are mainly used for the measurement of batteries at room temperature, 67,68 and are rarely used in the HTB studies. This is due to the fact that molten salt in HTBs, such as MSLBs, does not have the twisting effect of solvent molecules, resulting in a higher concentration of electrolytes than that in solutions.…”
Section: Infrared and Raman Spectramentioning
confidence: 99%